Transformation of Islamic Political Movements in Indonesia in the Reformation Era - Yani, Ahmad (STAI AL-FALAH CICALENGKA, 2023)
During the New Order era, there were only 3 political parties. After the New Order ended, proposals for the formation of political parties emerged. Before the 1999 elections were held, there were 181 political parties founded by various components of the nation. Of this number, 42 of them are Islamic parties. After passing the screening stage, only 48 parties were eligible and registered as participants in the 1999 elections, of which 20 were Islamic parties. Basic facts show that an important shift has occurred in Indonesia, namely a shift from state to political society, from bureaucrats to politicians. An equally dramatic change was the emergence of the da'wah movement and political Islam as the main force that attracted attention after being on the fringes of state power for so long. This research aims to determine the characteristics of Islamic parties, the history of Islamic politics, and the transformation of Islamic politics in the Reformation era. The research results show that the initial concept of a group changes, following the flow of local politics, but in fact it is a tool to achieve its goals and mission. Joining the Islamic group does not mean forgetting or abandoning its initial goals but could be an opportunity to gain wider public sympathy for the organization's expansion. There are strong indications of the emergence of symptoms of